2011
DOI: 10.1373/clinchem.2010.150854
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical and Asymmetrical Dimethylarginine as Predictors for Mortality in Patients Referred for Coronary Angiography: The Ludwigshafen Risk and Cardiovascular Health Study

Abstract: BACKGROUND Asymmetrical dimethylarginine (ADMA), an endogenous nitric oxide synthase inhibitor, has been linked to cardiovascular risk. The clinical role of its structural isomer symmetrical dimethylarginine (SDMA) remains largely unclear. METHODS We measured SDMA and ADMA in 3229 patients undergoing coronary angiography at baseline (1997–2000) and recorded total and cardiovascular mortality during a median follow-up time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 45 publications
4
104
2
1
Order By: Relevance
“…In another study, treatment with statins resulted in a significant reduction of markers of oxidative stress 13) . The structural isomer of ADMA, SDMA, has no effect on nitric oxide synthesis but is also related to cardiovascular events 14) . SDMA has also been shown to be an independent predictor of overall mortality after acute stroke 15) .…”
mentioning
confidence: 99%
“…In another study, treatment with statins resulted in a significant reduction of markers of oxidative stress 13) . The structural isomer of ADMA, SDMA, has no effect on nitric oxide synthesis but is also related to cardiovascular events 14) . SDMA has also been shown to be an independent predictor of overall mortality after acute stroke 15) .…”
mentioning
confidence: 99%
“…Other studies did not find a relevant increment in the C-statistic once ADMA or SDMA were added to the statistical prediction models in different clinical settings. [11,15,18,23,69] This concept also warrants further investigation. It needs to be established, however, whether inclusion of ADMA or SDMA improves risk prediction models (e. g. discrimination, reclassification) [81] beyond classic risk factors or that the increased risk for CVD and mortality associated with higher ADMA or SDMA can be specifically treated.…”
Section: Adma and Sdma Levels And Risk Prediction And Clinical Utilitymentioning
confidence: 91%
“…[9][10][11] However some conflicting results were observed; for example in the Framingham Offspring Study, ADMA was positively related to all-cause mortality, but not to incident CVD. [12] With respect to SDMA, initial studies did not find an association with adverse outcomes, [7,13,14] but some more recent studies reported positive associations with all-cause mortality or CVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of risk linked to SDMA is different from that linked to ADMA, suggesting different pathophysiological roles of these 2 methylarginine metabolites [10]. Because SDMA does not inhibit NOS, this structural isomer was thought to be inert [11].…”
Section: Introductionmentioning
confidence: 99%